Unique pattern of molt leads to low intraindividual variation in feather mercury concentrations in penguins. (14th August 2013) - Brasso, Rebecka L.; Drummond, Bridgette E.; Borrett, Stuart R.; Chiaradia, André; Polito, Michael J.; Rey, Andrea Raya
Abstract: The authors hypothesized that the catastrophic annual molt of penguins (Sphenisciformes) would lead to reduced intraindividual variation of mercury concentrations in body feathers. While mean mercury concentrations varied significantly among 8 penguin species, intraindividual variability did not differ among species and was 3 times lower than values observed in other seabirds. The findings of the present study suggest that a single body feather collected at random per individual can be adequate to estimate mercury exposure at the population level in penguins. Environ Toxicol Chem 2013;32:2331–2334. © 2013 SETAC